Interpersonal sensitivity, coping ways and automatic thoughts of nursing students before and after a cognitive-behavioral group counseling program. (January 2016) - Hiçdurmaz, Duygu; Öz, Fatma
Summary: Background: In order to provide optimal professional care to patients, nurses must possess a positive self-image and professional identity. High interpersonal sensitivity, coping problems and dysfunctional automatic thoughts can prevent nursing students to be self-confident and successful nurses. Helping nursing students experiencing interpersonal sensitivity problems via cognitive-behavioral counseling strategies can contribute to shape good nurses. Objectives: This study aims to evaluate interpersonal sensitivity, ways of coping and automatic thoughts of nursing students before and after a cognitive behavioral group counseling program. Design: An intervention study with 43 nursing students. Measurements were done before the counseling program, at the end of the program and 4.5 months after the program. Settings: The students were chosen from a faculty of nursing in Turkey. Participants: 43 second and third year nursing students who were experiencing interpersonal sensitivity problems constituted the sample. Methods: Brief Symptom Inventory, Ways of Coping Inventory and Automatic Thoughts Questionnaire were used for data collection. Results: The students' scores of "interpersonal sensitivity", "hopeless" and "submissive" copings and "automatic thoughts" were significantly lower at the end of and 4.5 months after the program than the scores before the program (Interpersonal sensitivity F = 52.903, p = 0.001; hopeless approach F = 19.213, p = 0.001; submissive approach F = 4.326, p = 0.016; automatic thoughts F = 45.471, p = 0.001). Scores of "self-confident", "optimistic" and "seeking social support" copings were higher at the end of and 4.5 months after the program than the scores before the program (Self confident F = 11.640, p = 0.001; optimistic F = 10.860, p = 0.001; seeking social support F = 10.411, p = 0.001). Conclusions: This program helped the students to have better results at interpersonal sensitivity, ways of coping and automatic thoughts at the end of and 4.5 months after the program. We have reached the aim of the study. We suggest that such counseling programs should be regular and integrated into the services provided for students. Highlights: We conducted a cognitive-behavioral group counseling program with 43 nursing students. We explored interpersonal sensitivity, ways of coping and automatic thoughts of the students before and after the program. Scores of "interpersonal sensitivity" and "automatic thoughts" were lower after the program. Scores of "hopeless" and "submissive" coping were lower after the program. Scores of "Self-confident", "optimistic" and "seeking social support" coping was higher after the program.